One-step catalytic cyclohexane oxidation to adipic acid using molecular oxygen - Yu, K; Hummeida, R; Abutaki, A; Tsang, S (2006)
Using combination of Mn-Co transition metal species with N-hydroxyphthalimide as a catalyst for one-step oxidation of cyclohexane with molecular oxygen in acetic acid at 353 K can give more than 95% selectivity towards oxygenated products with adipic acid as a major product at a high conversion (ca. 78%). A turnover number of 74 for this partial oxidation are also recorded. © Springer Science+Business Media, Inc. 2006.